2002
DOI: 10.1021/ja0202199
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Functionalized Asymmetric Benzynes with TMP-Zincates. Effects of Ligands on Selectivity and Reactivity of Zincates

Abstract: We have developed new methods for preparing functionalized benzynes through deprotonative zincation as a key reaction using R2Zn(TMP)Li, and we also describes dramatic ligand effects on the benzyne formation. Deprotonative zincation of various meta-substituted bromobenzenes with Me2Zn(TMP)Li proved effective for the one-pot generation of various 3-functionalized benzynes, particularly those electrophilic substituents such as ester, amide, and cyano. On the other hand, zincation with tBu2Zn(TMP)Li, followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
78
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(80 citation statements)
references
References 8 publications
1
78
1
Order By: Relevance
“…NMR ( 1 H, 7 Li, and 13 C) spectroscopic characterization of these crystals in a solution of deuterated benzene established the co-complexed nature of 1, as revealed most diagnostically in the chemical shift of the MÀCH 2 resonance of the MÀnBu linkage. This signal appears at d = 0.24 ppm in 1 relative to d = 0.27, À0.23, and À0.83 ppm in nBu 2 Zn, "[LinBu 3 Zn]", and nBuLi, respectively, thus suggesting that the nBu group in the new mixedmetal co-complex retains much of its original "zinc character". This last point was confirmed when the complete molecular structure of 1 was revealed through an X-ray crystallographic study ( Figure 1).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…NMR ( 1 H, 7 Li, and 13 C) spectroscopic characterization of these crystals in a solution of deuterated benzene established the co-complexed nature of 1, as revealed most diagnostically in the chemical shift of the MÀCH 2 resonance of the MÀnBu linkage. This signal appears at d = 0.24 ppm in 1 relative to d = 0.27, À0.23, and À0.83 ppm in nBu 2 Zn, "[LinBu 3 Zn]", and nBuLi, respectively, thus suggesting that the nBu group in the new mixedmetal co-complex retains much of its original "zinc character". This last point was confirmed when the complete molecular structure of 1 was revealed through an X-ray crystallographic study ( Figure 1).…”
mentioning
confidence: 99%
“…Established only in 1999 through the pioneering work on "[LitBu 2 Zn(tmp)]" by Kondo et al, [1] "tmp zincates" have found application as highly chemo-and/or regioselective bases for the metalation of alkyl benzoates and related aza aromatic compounds, bromopyridines, and various halobenzenes. [2,3] Recent reports [4] have highlighted the poverty of structural information available on lithium zincates in general. Tmp zincates are no exception in this regard, with a 13 C NMR spectroscopic study of "[LitBu 2 Zn(tmp)]" in solution [1] providing the only morsel of structural evidence…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, if its ability to acidify the adjacent hydrogens is good, both from a kinetic and a thermodynamic point of view, [2] the ortho-bromoarylmetals formed are prone to benzyne formation. Such a limitation can be overcome either by using lithium-metal bases such as TMP-zincate ( t Bu 2 Zn(TMP)Li, TMP = 2,2,6,6-tetramethylpiperidino), [3] or using in situ electrophilic trapping, [4] or even in the presence of another substituent (e.g. CF 3 [5] ), capable of stabilizing the arylmetal compound.…”
mentioning
confidence: 99%